The challenge to transform learning: Changing teachers’ theory of teaching - Hin, Lim Chong; Ratnavadivel, Nagendralingan; Yassin, Sopia Md; Saad, Noor Shah; Nagappan, Rajendran; Saravanan, Idris Md (Journal of Research, Policy & Practice of Teachers and Teacher Education, 2018)
There is widespread concern in Malaysia about the quality of learning experienced by students, and the approach to learning they develop as a consequence. The approach is generally marked by memorization of information as isolated facts and does not promote understanding or long-term retention of knowledge and information. Despite a number of large-scale, centrally-driven reform efforts to change the status quo, they have for the most part met with little success. Based on the data collected as part of a nation-wide study to investigate the way teachers make pedagogical decisions, this paper argues that one major challenge to transform students‟ approach to learning is changing the way teachers think about teaching which past reform efforts have largely ignored. The data suggest that the teachers studied mainly see teaching as transmitting information from teacher to the student. In this view of teaching they hold, they focus their attention on the differences between students to explain differences in learning. Learning is therefore not seen as more a function of what the teacher does than what a student is. This means, unless their view of teaching in challenged, their teaching is unlikely to change to be more responsive and supportive of student learning. The data for this study was collected through qualitative approaches involving interviews and classroom observation. The findings of the study have wide implications in planning professional development courses for teachers to transform the way students learn.